Science, Power, and Democracy: A Critical Perspective of Political Influence on Knowledge Production - Islami, Moch Zihad; Muthmainnah, Lailiy (Jurnal Filsafat "WISDOM", 2025)
This study aims to explore the relationship between science, power, and democracy. This relationship stems from the fundamental argument that science is always linked to values, whether political, ideological, or even economic interests. While science can contribute positively to transforming public life for the better, it can also give rise to exclusivity and elitism in the scientific community, which can undermine democratic principles and values. This study demonstrates that the relationship between science and politics is ambivalent, as it can both strengthen the legitimacy of public governance and create the risk of technocracy and expert dominance, leading to the public being perceived as lacking adequate epistemic capacity in certain scientific fields. Therefore, efforts are needed to steer science toward a true public interest through the democratization of science, both procedurally and substantively. However, normative boundaries remain crucial: when emerging public values are discriminatory, scientists are obligated to reject them, as they contradict the egalitarian principles that underlie democracy. Furthermore, public trust in science must be maintained by ensuring that the public is fully imagined and involved in the knowledge production process. Thus, public-oriented science must be committed to the values of humanity and equality.